RELIGIOUSITY IN THE STORY â€œA DEER THAT ALWAYS REMEMBERS GODâ€: FABLE FROM SUNDA LAND - Atisah, Atisah (ppjbsip, 2021)
This paper aims to analyze and reveal the values of religiosity in the animal story or fable